A Quantitative Method for Evaluating Contemporary Cultural Uses of Birds: A Case Study from Mexico - Ávila-Nájera, Dulce María; Tigar, Barbara J.; Zavala-Sánchez, Zaira; Zetina-Cordoba, Pedro; Serna-Lagunes, Ricardo (Ethnobiology Letters, 2020)
This study evaluates the relationship between people and birds in Mexico, a country where high cultural and biological diversity are reflected in the close associations between people and natural resources, recorded since pre-Hispanic times. It systematically reviews 1041 records of cultural use of wild birds in Mexico published between 1996–2017 and analyzes patterns of contemporary use of avifauna. It classifies information for 252 birds by grouping uses of species and families into 11 categories and quantifies overall use with a Cultural Value Index (CVI). The data show that birds have a high cultural value as food, pets, and for medicinal uses (312, 235, and 119 records, respectively), particularly in the state of Chiapas. Large edible birds had the highest CVIs and included Plain chachalacas (Ortalis vetula; 9.72), Black-bellied whistling-ducks (Dendrocygna autumnali; 6.65), Crested guams (Penelope purpurascens; 6.25), and Great currasows (Crax rubra; 6.23), with the Cracidae family recorded as favored gamebirds. Conspicuous, brightly-colored birds had high CVIs, including Keel-billed toucans (Ramphastos sulfuratus; 6.50), Red-lored amazons, (Amazona autumnalis; 6.03), and allied species, which were traded or kept as pets despite legal protection. The high CVIs of Barn owls (Tyto alba; 5.45) were related to medicinal uses, and Mourning doves (Zenaida macroura; 5.69) were mainly used as gamebirds. Wild bird populations face increasing pressure from habitat loss and overexploitation. We propose that evaluating the ethnological significance of wildlife with indices like CVIs can quantify the distinctive needs of rural communities, which when combined with information on conservation status can develop more sustainable species management plans.